2001
DOI: 10.1177/089124240101500205
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Effectiveness of Louisville’s Enterprise Zone

Abstract: Louisville, Kentucky, has one of the oldest and largest enterprise zones (EZs) in the United States, yet until recently, the program had not been independently evaluated. Perhaps because no clearly superior evaluation methodology has emerged in the literature, the efficacy of EZ programs around the United States remains a contentious subject among scholars and policy makers alike. The authors take a quasi-experimental approach in evaluating Louisville’s EZ, using many different measures to give the program eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(54 citation statements)
references
References 5 publications
6
48
0
Order By: Relevance
“…Therefore, it is assumed that 1980 to 1990 and 1990 to 2000 are preprogram and postprogram periods; that is, without and with treatment periods. The study of Lambert and Coomes (2001) further confirms that no effects were observed over 1980 to 1990. Table 1 presents the qualification requirements and benefits for firms located inside an EZ.…”
Section: Louisville Enterprise Zone Programsupporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, it is assumed that 1980 to 1990 and 1990 to 2000 are preprogram and postprogram periods; that is, without and with treatment periods. The study of Lambert and Coomes (2001) further confirms that no effects were observed over 1980 to 1990. Table 1 presents the qualification requirements and benefits for firms located inside an EZ.…”
Section: Louisville Enterprise Zone Programsupporting
confidence: 88%
“…Then, the section titled "Data Preparation" discusses several data-related issues and is followed by a shift-share (SS) analysis and results. The 1990 regional shifts are quite consistent with Lambert and Coomes (2001) in that industries in non-EZ areas tend to be more competitive than industries in EZ areas. A comparison of the 1990 and 2000 regional shifts, however, reveals that non-EZ areas are losing strength, whereas industries in EZ areas are growing stronger.…”
supporting
confidence: 76%
“…There has been an extensive body of research into the impact of the policy in the USA. Examples include the work of Papke (1993Papke ( , 1994, Boarnet and Bogart (1996), Engberg and Greenbaum (1999), Bondonio and Engberg (2000), Lambert and Coombes (2001), Boarnet (2001), HUD (1997), O'Keefe (2004), Greenbaum and Engberg (2004), Rogers and Tao (2004), Busso and Kline (2008), Krupa and 68 S.A. Bond et al Noonan (2009) and Hanson (2009).…”
Section: Introductionmentioning
confidence: 97%
“…In contrast, Lambert and Coomes (2001) provided a detailed analysis of Louisville's enterprise zone. They used a quasi-experimental analysis comparing various socioeconomic indicators for Louisville's EZ with similar regions in the same county and found that the Louisville EZ is not particularly effective.…”
Section: Effects Of Property Tax Abatementsmentioning
confidence: 99%